Adolescents’ Knowledge and Attitude Before and After Exposure to Media of Youth Sexual Behavior in Indonesia - Setyafanny Santoso1 , Pulung Siswantara1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The increasing number of cases regarding adolescent free sex is due to a lack understanding of reproductive health. Someone’s knowledge about reproductive health is believed to be closely related to what action they take. In the context of adolescence, their knowledge of reproductive health undoubtedly influences their attitude toward premarital sex. Most of premarital sex cases occur because they are lacking of knowlegde about its impact. This quasi-experiment was consucted on a senior high school in Indonesia. Subjects were 144 nine grade students, selected using purposive random sampling from a total population of 229 students. For each control and experiment groups, 72 students each were selected. The experiment group participated in the treatment of the study. Data was analyzed using paired t-test to find the differences of control and experiment groups’ knowledge and attitude. Both groups showed an increase of knowledge. However, the increase in experiment groups were more than one of the control group. There were only 10 students (14%) of experiment groups reached the category of having good understanding on the pre test and the number increased on the post to 39 students (54%).